Navigating Pluralism in Islamic Jurisprudence: A Comparative Analysis of Mut'ah Marriage in Ja'fari and Sunni Schools of Thought - Azhari, Doni; Asmuni, Asmuni; Nasution, Khoiruddin (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2024)
This study examines the differing views on mut'ah (temporary) marriage between the Ja'fari and Sunni schools of Islamic jurisprudence through a comparative analysis of their legal reasoning methodologies. Employing qualitative research methods including textual analysis of primary sources, historical examination, and comparative legal analysis, the study explores the origins of these divergent interpretations and their implications for contemporary Muslim societies. The findings reveal that differences in scriptural interpretation, hadith authentication, and legal principles contribute to the contrasting positions on mut'ah marriage. While the Ja'fari school considers it permissible based on Quranic verses and certain hadith, Sunni schools generally prohibit it, citing abrogation and potential social harms. The study highlights how these differing views reflect broader patterns of legal pluralism in Islamic jurisprudence and impact contemporary debates on gender, marriage, and religious authority in Muslim communities. By critically evaluating arguments from both traditions, this research contributes to a more nuanced understanding of Islamic legal diversity and its ongoing negotiation in modern contexts.